FAKTOR – FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT PADA PERUSAHAAN PROPERTIES DAN REAL ESTATE - Tasya Clarissa; Utoyo Widayat (Jurnal Paradigma Akuntansi, 2026)
This research aims to obtain empirical evidence regarding the effect of auditor tenure, auditor size, auditor switching, and total asset growth on audit quality in properties and real estate sector companies on the IDX for the 2018-2021 period. The sample used in this research was selected by purposive sampling method with valid data as many as 46 companies. The data processing technique used in this research is logistic regression analysis using the Eviews application version 12 and Microsoft Excel 2010. The results of this research indicate that auditor tenure and auditor switching have a significant influence on audit quality. Meanwhile, auditor size and total asset growth do not have a significant effect on audit quality. The implications obtained from this research are the need for awareness from both the client and the auditor to pay attention to tenure auditors and conduct auditor switching to the procedures needed to maintain skepticism of both parties and improve audit quality in companies.